Coactive Vicarious Learning: Toward a Relational Theory of Vicarious Learning in Organizations - Myers, Christopher G. (Academy of Management Review, 2018)
Vicarious learning—individual learning that occurs through being exposed to and making meaning from another's experience—has long been recognized as a driver of individual, team, and organizational success. Yet existing perspectives on this critical learning process have remained fairly limited, often casting vicarious learning as simply an intrapersonal, one-way process of observation and imitation. Largely absent in prior perspectives is a consideration of the relational dynamics and underlying behaviors by which individuals learn vicariously through interacting with others, rendering these perspectives less useful for understanding learning in the increasingly interconnected work of modern organizations. Integrating theories of experiential learning and symbolic interactionism, I offer a theoretical model of coactive vicarious learning, a relational process of coconstructed, interpersonal learning that occurs through discursive interactions between individuals at work. I explore how these interactions involve the mutual processing of another's experience; are influenced by characteristics of the individual, relational, and structural context in organizations; and lead to growth not only in individuals' knowledge but also in their individual and relational capacity for learning and applying knowledge. I close by discussing the implications of this conceptual model for the understanding and practice of vicarious learning in organizations.